Financial enterprise risk management - Sweeting, Paul. (Cambridge ; New York : Cambridge University Press, 2011)
"Financial Enterprise Risk Management provides all the tools needed to build and maintain a comprehensive ERM framework. As well as outlining the construction of such frameworks, it discusses the internal and external contexts within which risk management must be carried out. It also covers a range of qualitative and quantitative techniques that can be used to identify, model and measure risks, and describes a range of risk mitigation strategies. Over 100 diagrams are used to help describe the range of approaches available, and risk management issues are further highlighted by various case studies. A number of proprietary, advisory and mandatory risk management frameworks are also discussed, including Solvency II, Basel III and ISO 31000:2009. This book is an excellent resource for actuarial students studying for examinations, for risk management practitioners and for any academic looking for an up-to-date reference to current techniques"--
An introduction to enterprise risk management -- Types of financial institution -- Stakeholders -- The internal environment -- The external environment -- Process overview -- Definitions of risk -- Risk identification -- Some useful statistics -- Statistical distributions -- Modelling techniques -- Extreme value theory -- Modelling time series -- Quantifying particular risks -- Risk assessment -- Responses to risk -- Continuous considerations -- Economic capital -- Risk frameworks -- Case studies.
Περιέχει βιβλιογραφία και ευρετήριο.
Keywords: Financial institutions -- Risk management; Financial services industry -- Risk management